Which of the following are solutions to the equation below?check all that apply. x^2+6x+9=6
A. x=3+√6
B. x=3-√6
C. x=3
D. x=0
E. x=-3+√6
F. x= -3-√6

Answers

Answer 1
Answer: make it equal to zero
minus 6 from both sides
x^2+6x+3=0
quadratic formula
x=\frac{-b+/- \sqrt{b^(2)-4ac} }{2a}


x=\frac{-6+/- \sqrt{6^(2)-4(1)(3)} }{2(1)}
x=(-6+/- √(36-12) )/(2)
x=(-6+/- √(24) )/(2)
x=(-6+/- 2√(6) )/(2)
x=-3+/- √(6)


E and F are answer


Related Questions

Algebra Homework Question
When 80% of a is added to the number, the result is 252. What is the number
The total operating cost for the truck is $400 000 per year. The percentage breakdown of this total amount was:40%: Fixed costs (insurance, registration, wages) 30%: Fuel 20%: Finance 10%: Maintenance (service, repairs, tyres) Suppose the fuel price increases from $1.50 to $1.60 per litre. How much does this add to the total operating cost per year?
5 over 9 - 1 over 3 x 1 over 6
Look at the linear equation below.2x - 3y = -13Which pair of numbers is a solution to the equation?Select one:(-5, 1)(5, 1)(5, -1)(-5, -1)

Help me yaall for 17 point

Answers

8, look at the attachment for work

Which of the following equations represent the Pythagorean theorem?A. c =
\sqrt{ {a}^(2) }  +  {b}^(2)
B. m =
(y2  - y1)/(x2 - x1)
C. c= a+b
D. ab=ba

Answers

There's no equation represent the pythagorean theorem in the options. The option A is closed to pythagorean theorem, except the b² should be under root.

Pythagorean Theorem is supposed to be like this
c= \sqrt{a^(2)+b^(2)}

Simplify the expressing by combining like terms
1 + 3x - 8x + 7​

Answers

\huge\text{Hey there!}

\large\textsf{1 + 3x - 8x + 7}

\large\text{COMBINE the LIKE TERMS }

\large\textsf{ (3x - 8x) + (1 + 7)}

\large\textsf{3x - 8x = \bf -5x}

\large\textsf{1 + 7 = \bf 8}

\large\textsf{= -5x + 8}

\boxed{\boxed{\large\text{Answer: \huge \bf -5x + 8}}}\huge\checkmark

\text{Good luck on your assignment and enjoy your day!}

~\frak{Amphitrite1040:)}

Combining like terms with negative coefficients
2x-4xy+5x-2xy-4x-4y?

Answers

Answer: 3x-6xy-4y

Step-by-step explanation: So, it’s been a few years since I’ve been in high school, but if I remember correctly...it should break down as such...

A good method to breaking this down is to use parentheses to break up the equation.

Example: (2x)(-4xy)(+5x)(-2xy)(-4x)(-4y)

Keep in mind we are only using the parentheses as a breaker and not as multiplication as it can be seen.

So, start with the singular ‘x’ variants. (2x) (+5x) (-4x). 2x+5x is 7x. 7x-4x is 3x. Now, move onto ‘xy’ variant. (-4xy) and (-2xy). As these are both negative, they add together to make an even lower number...being -6xy. Onto the final step taking the singular ‘y’ variant. There’s only 1 ‘y’ variant so it just stays -4y.

In the end, you end up with 3x-6xy-4y. :) Hope this helps. If you have any more questions, let me know!

67885 truing 6788 yea that ab it

A certain alloy contains 5.25% copper. How much copper is there in a piece weighing 200 pounds?

Answers

There are 10.5 pounds of copper in a piece weighing 200 pounds.

We have,

The concept used to calculate the amount of copper in a piece weighing 200 pounds is the concept of percentage.

Now,

5.25 pounds of copper is to 100 pounds of alloy as x pounds of copper is to 200 pounds of alloy.

To determine the amount of copper in a piece weighing 200 pounds, we need to calculate 5.25% of 200 pounds.

To do this, we multiply 5.25% (or 0.0525) by 200:

0.0525 * 200 = 10.5

Therefore,

There are 10.5 pounds of copper in a piece weighing 200 pounds.

Learn more about percentages here:

brainly.com/question/11403063

#SPJ6

The 200-pound piece of alloy contains 10 and a 1/2 pounds of copper.

14 1/4 - 10 3/7 Reduce to lowest form....
step by step to see if my answer your answer

Answers

14 (1)/(4)= (14\cdot4+1)/(4)= (57)/(4)

10 (3)/(7)= (10\cdot7+3)/(3)= (73)/(7)

\hbox {So, you have now }  (57)/(4)-(73)/(7)=(57\cdot7)/(4\cdot7)-(73\cdot4)/(7\cdot4)= (399)/(28)-(292)/(28)=\boxed {(107)/(28) }=\boxed { 3(23)/(28) }
make them improper fractions:
14 1/4 would be 57/4
10 3/7 would be 73/7
Make them the same common denominator:
Times 57/4 by 7/7 =399/28
Times 73/7 by 4/4 =292/28
Now subtract them:
107/28 
Now Simplify:
107/28= (3*28+23)/28=3+23/28= 3 23/28
The Answer:
3 23/28